Bridging the mismatch: observing the introduction of new anesthesia technology for a low-resource environment - Sampson, John Burthorne; Koka, Rahul; Tomobi, Oluwakemi; Chima, Adaora; Jackson, Eric Vincent; Rosen, Michael; Koroma, Michael; Nelson-Williams, Howard; David, Elizabeth; Lee, Benjamin (Frontiers in Medicine, 2024)
Objective The objective of this study was to examine the impact of the introduction of the Universal Anaesthesia Machine (UAM), a device designed for use in clinical environments with limited clinical perioperative resources, on the choice of general anesthesia technique and safe anesthesia practice in a tertiary-care hospital in Sierra Leone. Methods We introduced an anesthesia machine (UAM) into Connaught Hospital, Freetown, Sierra Leone. We conducted a prospective observational study of anesthesia practice and an examination of perioperative clinical parameters among surgical patients at the hospital to determine the usability of the device, its impact on anesthesia capacity, and changes in general anesthesia technique. Findings We observed a shift from the use of ketamine total intravenous anesthesia to inhalational anesthesia. This shift was most demonstrable in anesthesia care for appendectomies and surgical wound management. In 10 of 17 power outages that occurred during inhalational general anesthesia, anesthesia delivery was uninterrupted because inhalational anesthesia was being delivered with the UAM. Conclusion Anesthesia technologies tailored to overcome austere environmental conditions can support the delivery of safe anesthesia care while maintaining fidelity to recommended international anesthesia practice standards.